Effects of khat (Catha edulis) chewing on dry mouth and taste function: A comparative cross-sectional study - Ola Mohsen Al-Akwa'a (21153305) (2025)
Objectives To evaluate oral dryness and the taste sensation threshold (sweet, salt, sour, bitter) among khat chewers. Method This cross-sectional comparative study enrolled 140 healthy individuals divided into two groups: khat chewers (KC; n = 73), and non-chewers (NC; n = 67). Oral dryness was assessed using the Clinical Oral Dryness Score (CODS), while taste perception was assessed using the four primary tastes: sweet, salt, sour, bitter, along with the Total Taste Score (TTS), each prepared as seven chemical solutions representing seven concentrations. SPSS V. 26 was used for data analysis. Results Overall, KC revealed significantly higher overall CODS scores compared to NC (4.26±1.39 vs. 2.10±1.15; P < 0.001). The TTS was significantly lower in KC (16.52 ± 3.367) compared to NC (18.87 ± 3.592; P < 0.001), owing to revealing significantly lower mean taste sensation scores for sweet, salty, and bitter tastants, but not for sour taste. Up to 20.5% of KC had hypogeusia compared to only 4.5% of NC (P = 0.005). Multivariate analyses also revealed khat chewing as an independent determinant factor for oral dryness and hypogeusia. Conclusion Chronic khat chewing is associated with mouth dryness and taste impairment, gravely impacting on the patients’ quality of life. Other Information Published in: Oral Surgery, Oral Medicine, Oral Pathology and Oral Radiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.oooo.2025.03.016